Pengaruh Kualitas Pelayanan Terhadap Event Image Sari Wisata Budaya Bali Sebagai Daya Tarik Incentive - Damayanti, Ni Kadek Dwi; Swandewi, Ni Kadek (Journal of Tourism and Hospitality Analysis (JoTHA), 2025)
This study aims to analyze the influence of service quality on the event image of Sari Wisata Budaya Bali as an incentive atraction. Sari Wisata Budaya Bali is a cultural attraction that regularly features Barong Dance performances, presented as part of its cultural events. The research employs a quantitative approach using a survey method, involving 100 respondents who visited Sari Wisata Budaya Bali in 2024. The data were analyzed using multiple linear regression, with five dimensions of service quality tangibles, reliability, responsiveness, assurance, and empathy, serving as independent variables, and event image as the dependent variable. The findings indicate that the five dimensions of service quality collectively have a significant influence on the event image, contributing 65.3%, while the remaining variance is attributed to factors beyond the scope of this study. Among these dimensions, empathy emerged as the most dominant factor influencing visitors’ perceptions of the event. Responsiveness showed the highest individual impact, with a coefficient of 0.323, whereas tangibles had the lowest, at 0.118.